Identification of foodborne pathogenic bacteria using confocal Raman microspectroscopy and chemometrics - Zhang, Jin; Gao, Pengya; Wu, Yuan; Yan, Xiaomei; Ye, Changyun; Liang, Weili; Yan, Meiying; Xu, Xuefang; Jiang, Hong (Frontiers in Microbiology, 2022)
Rapid and accurate identification of foodborne pathogenic bacteria is of great importance because they are often responsible for the majority of serious foodborne illnesses. The Confocal Raman microspectroscopy (CRM) is a fast and easy-to-use method known for its effectiveness in detecting and identifying microorganisms. This study demonstrates that confocal Raman microspectroscopy (CRM) combined with chemometrics can serve as a rapid, reliable and efficient method for detection and identification of foodborne pathogenic bacteria without any laborious pre-treatments. Six important foodborne pathogenic bacteria including S. flexneri, L. monocytogenes, V. cholerae, S. aureus, S. typhimurium and C. botulinum were investigated with CRM. These pathogenic bacteria can be differentiated based on several characteristic peaks and peak intensity ratio. Principal component analysis (PCA) was used for investigating the difference of various samples and reducing the dimensionality of dataset. Performances of some classical classifiers were compared for bacteria detection and identification including Decision Tree (DT), Artificial Neural Network (ANN) and Fisher discriminant analysis (FDA). Correct recognition ratio (CRR), area under the receiver operating characteristic curve (ROC), Cumulative gains and Lift charts were used to evaluate performance of models. The impact of different pretreatment methods on the models was explored, pretreatment methods include Savitzky-Golay algorithm smoothing (SG), standard normal variate (SNV), multivariate scatter correction (MSC) and Savitzky-Golay algorithm 1st Derivative (SG 1st Der). In the DT, ANN and FDA model, FDA is more robust for overfitting problem and offers the highest accuracy. Most pretreatment methods raised the performance of the models except SNV. The results revealed that CRM coupled with chemometrics offer a powerful tool for the discrimination of foodborne pathogenic bacteria.